Temporal trends and yield of clinical diagnostic genetic testing in adult neurology. Issue 10 (2nd June 2021) - Guo, Michael H.; Bardakjian, Tanya M.; Brzozowski, Morgan R.; Scherer, Steven S.; Quinn, Colin; Elman, Lauren; Orthmann‐Murphy, Jennifer; Tropea, Thomas F.; Ellis, Colin A.; Gonzalez‐Alegre, Pedro
Abstract: While genetics evaluation is increasingly utilized in adult neurology patients, its usage and efficacy are not well characterized. Here, we report our experience with 1461 consecutive patients evaluated in an adult neurogenetics clinic at a large academic medical center between January 2015 and March 2020. Of the 1461 patients evaluated, 1215 patients were referred for the purposes of identifying a genetic diagnosis for an undiagnosed condition, 90.5% of whom underwent genetic testing. The modalities of genetic testing utilized varied across referral diagnostic categories, including a range of utilization of whole exome sequencing (WES) as an initial test in 13.9% of neuromuscular patients to 52.9% in white matter disorder patients. The usage of WES increased over time, from 7.7% of initial testing in 2015 to a peak of 27.3% in 2019. Overall, genetic testing yielded a causal genetic diagnosis in 30.7% of patients. This yield was higher in certain referring diagnosis categories, such as neuromuscular (39.0%) and epilepsy (29.8%). Our study demonstrates that evaluation at an adult neurogenetics referral center can yield diagnoses in a substantial fraction of patients. Additional research will be needed to determine optimal genetic testing strategies and cost effectiveness of adult neurogenetics evaluation.